Total phenolic content in piper sarmentosum using different extraction techniques and solvents: a short review - Ibrahim, Maizatul Akma; Kamarul Arifin, Nuryn Imanina; Mohd Hasali, Nor Hazwani (Wolters Kluwer, 2022)
Piper sarmentosum is an herbaceous plant that belongs to Piperaceae family which possesses an antioxidant activity due to the presence of phenolic compounds. The extraction of phenolic compounds from this Piper species could be carried out by employing various conventional and nonconventional extraction techniques and solvents. Among the extraction techniques commonly applied are maceration, infusion, reflux, and water bath extraction which are classified as conventional methods. Meanwhile, among nonconventional approaches employed are microwaved‑assisted extraction, ultrasonic‑assisted extraction (UAE), microwave‑assisted infusion, and agitation extraction. The recovery of phenolic content could be performed using different extracting solvents such as water, ethanol, methanol, butanol, hexane, n‑hexane, acetone, chloroform, and ethyl acetate. In this manuscript, the effect of different extraction techniques and solvents on the total phenolic content (TPC) in P. sarmentosum was reviewed. Previous research recorded that the TPC which was expressed as gallic acid equivalent in P. sarmentosum ranges from 0.57 mg GAE/g for UAE to 430 mg GAE/g where the maceration technique produced the highest TPC. While for the extracting solvents, methanol gave the most significant amount of TPC with obtained value at 379 mg GAE/100 g. This research provides an overall review of different techniques of solvents which could be used as references on the optimization of extraction processes to enhance the recovery of phenolic content from P. sarmentosum.